Learning about brands: a study of the changes in the nature of consumers’ brand associations over time. - Goh, Sumi. (2008)
Our focus is on whether adults’ learning is dominated by benefit/value information. Our research found that the nature of brand associations indeed change as a brand becomes established. Conclusions are then drawn about how marketers should monitor and promote appropriate features of their brand as their product becomes established.